KONTESTASI PENYIARAN AGAMA DI RUANG PUBLIK: RELASI KRISTEN DAN ISLAM DI KOTA JAYAPURA - Zuly Qodir (Harmoni, 2015)
In Indonesia religious contestation emerges in interreligious groups. It occurs in Jayapura. Some people claim that indigenous people of Papua that are christians called mountain people but Muslims that live in beach or on land are not native people of Papua. The contestation happens in public spaces such as public field, mountain, street, and religious practices by exerting a mass of people to have Christian revival worship and conduct Tablighi Akbar for muslims. Both muslims and christians invite the speakers from outside Papua to attract others. Contestation occurs since 1998 until now. It can be seen from large demonstration and a ban of religious practices and the establishment of Islamic schools. Many problems that come from internal and external of adherent are found in Papua. The data collection consists of direct observation, interviews, literature reviews, and relevant document. The data employs interpretative approach conducted by Clifford Geertz in sociology and anthropology or the other social science in general.